ANALYSIS OF INTENSIVE CARE RESULTS IN PREGNANT WOMEN WITH SEVERE FORM OF TUBERCULOSIS - V. B. Tskhay; A. M. Polstyanoy; G. V. Gritsan; A. I. Gritsan; G. N. Polstyanaya (Акушерство, гинекология и репродукция)
The article presents analysis of intensive care results in 32 pregnant women diagnosed with tuberculosis for the period from 2009 to 2013. The average age of the patients was 28.4±5.6 years; gestational age - 34.3±7.5 weeks. It was determined that 90.6% of pregnant women with severe forms of tuberculosis during the treatment were carried out surgical delivery in relation to the severity of the pulmonary process, at the average gestational age +21 weeks. The finding says that pregnancy and postpartum period in patients with severe forms of tuberculosis were accompanied by obstetric complications of pregnancy in 59.3% of cases and septic complications in 29.3% of cases. It is shown that integrated management and intensive treatment of pregnant women with severe forms of tuberculosis make possible to ensure the survival of 81.2% of the patients